Disaggregating China, Inc. : state strategies in the liberal economic order - Tan, Yeling (Cornell studies in political economy., 2021)
"This book examines the impact of entry into the World Trade Organization (WTO) on China's domestic economic governance. It shows that rather than constraining the state, WTO entry provoked a divergence of policy responses, intensifying political contests between bureaucratic and political actors inside China's authoritarian structure"--